PEMANFAATAN AIR LIMBAH REBUSAN IKAN TAMBAN (Sardinella sp.) SEBAGAI FLAVOR PASTA ALAMI - Muhamad Syahrul Syah; Azwin Apriandi; R. Marwita Sari Putri (Marinade, 2020)
The aims of this study was to determine the effect of temperature on the level of preference of panelists resulting from flavor paste. This research is an experimental laboratories with a completely randomized design of one factor, namely wastewater boiled fish is treated with different temperatures with a temperature of 70 °C, 75 °C, 80 °C, 85 °C, 90 °C. Then analyzed using SPSS 25 to obtain the best treatment. The results of the experiment showed that falvor paste given different treatment gave a significant difference (